2021
DOI: 10.3390/su13094904
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of CSR Performance and Voluntary CSR Disclosure Extent in the German DAX Indices

Abstract: Empirical studies present mixed evidence on the relationship of CSR performance and CSR disclosure extent, thus spurring academic ambiguity as legitimacy- and voluntary disclosure theory provide competing explanations. By applying content analysis to 144 voluntary GRI reports of listed firms in Germany from 2015 to 2018, I construct environmental and social disclosure indices to capture the reports’ disclosure extents. The contents are extracted from the corresponding GRI content indices in order to mitigate p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 119 publications
(182 reference statements)
0
5
0
Order By: Relevance
“…Much of the pre-COVID-19 interdisciplinary research on CSR and corporate law has emphasised the importance of mandatory CSR and proposed a regulatory framework enforced by corporate law and governance mechanisms [13][14][15]. However, scholars have made few attempts to differentiate between ex ante and ex post CSR law approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the pre-COVID-19 interdisciplinary research on CSR and corporate law has emphasised the importance of mandatory CSR and proposed a regulatory framework enforced by corporate law and governance mechanisms [13][14][15]. However, scholars have made few attempts to differentiate between ex ante and ex post CSR law approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Companies with better CSR performance are more likely to publish more CSR reports (Uyar et al 2020). Environmental performance is positively related to environmental disclosure, while social performance is not related to social disclosure (Danisch 2021). It has also been found that environmental performance is negatively related to environmental disclosure (Doan and Sassen 2020).…”
Section: Intrinsic Dynamics Of Esg Disclosurementioning
confidence: 96%
“…Among the sustainability accounting literature, some of them have explored the relationship between sustainability reporting practices and sustainability performance. Based on a sample of German listed firms, Danisch (2021) finds that environmental performance is associated with environment reporting practices. Danisch (2021) believes that firms with good environmental performance use high environment reporting practices to signal their superior quality in environment protection.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Based on a sample of German listed firms, Danisch (2021) finds that environmental performance is associated with environment reporting practices. Danisch (2021) believes that firms with good environmental performance use high environment reporting practices to signal their superior quality in environment protection. Al‐Tuwaijri et al (2004) explore the relationship between environmental performance and environment reporting practices in the American context in 1994 and a positive relationship is identified.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation